WARIS SAMA RATA DALAM KELUARGA MUSLIM INDONESIA: ANALISIS NORMATIF PERKEMBANGAN HUKUM WARIS ISLAM: Equal Inheritance in Indonesian Muslim Families: A Normative Analysis of the Development Islamic Inheritance Law - Rahel Matilda Thin Payung; Wahyuni Retnowulandari (Faculty of Law, Universitas Trisakti, 2026)
Indonesian Islamic inheritance law normatively regulates the distribution of inheritance between sons and daughters at a ratio of 2:1, as stipulated in Surah An-Nisa verse 11 and Article 176 of the Compilation of Islamic Law. However, in practice, several religious court decisions in Indonesia have found equal distribution of inheritance. The research question is whether the equal distribution of inheritance between sons and daughters is permissible under Islamic inheritance law. The type of research used is normative, focusing on the principles of Islamic inheritance law. It is descriptive in nature, using secondary data that includes primary and secondary legal materials, which are then processed qualitatively with deductive conclusions. The results and conclusion of the discussion show that the development of Indonesian Islamic inheritance law is reflected in the practice of equal inheritance distribution, which is realized with several legal considerations without necessarily disregarding the applicable faraidh provisions. Equal inheritance distribution can be carried out with the agreement and deliberation of each heir, resulting in peace.